1977 - 1987 : Catalogue of Collection : Sculpture 1977-1987. (Osake : The National Museum of Art, 1987)
Calder, Alexander ; Segal, George ; Kusama, Yayoi ; Nagasawa, Hidetoshi ; César ; Johns, Jasper ; Moore, Henry ; Noguchi, Isamu ; Zadkine, Ossip ; Iida, Hoshikuni ; Oda, Jo ; Kimura, Kentaro ; Sato, Churyo ; Shimizu, Seiji ; Sumiya, Masami ; Tada, Minami ; etc.
Engels & Japans
boek